An experimental study of charity hazard: The effect of risky and ambiguous government compensation on flood insurance demand - Peter John Robinson; W.J. Wouter Botzen; Fujin Zhou (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
This paper examines the problem of "charity hazard", which is the crowding out of private insurance demand by government compensation. In the context of flood insurance and disaster financing, charity hazard is particularly worrisome given current trends of increasing flood risks as a result of climate change and more people choosing to locate in high-risk areas. We conduct an experimental analysis of the influence on flood insurance demand of risk and ambiguity preferences and the availability of different forms of government compensation for disaster damage. Certain and risky government compensation crowd out demand, confirming charity hazard, but this is not observed for ambiguous compensation. Ambiguity averse subjects have higher insurance demand when government compensation is ambiguous relative to risky. Policy recommendations are discussed to overcome charity hazard
Keywords: 330; Ambiguity preferences; charity hazard; economic experiment; flood insurance demand; risk preferences